Unresectable stage III non-small cell lung cancer: could durvalumab be safe and effective in real-life clinical scenarios? Results of a single-center experience - Borghetti, Paolo; Volpi, Giulia; Facheris, Giorgio; Cossali, Gianluca; Mataj, Eneida; La Mattina, Salvatore; Singh, Navdeep; Imbrescia, Jessica; Bonù, Marco Lorenzo; Tomasini, Davide; Vitali, Paola; Greco, Diana; et al. (Frontiers in Oncology, 2023)
Introduction: The standard of care for patients with unresectable stage III non-small cell lung cancer (NSCLC) is chemoradiotherapy (CRT) followed by consolidation Durvalumab as shown in the PACIFIC Trial. The purpose of this study is to evaluate clinical outcomes and toxicities regarding the use of Durvalumab in a real clinical scenario. Methods: A single-centre retrospective study was conducted on patients with a diagnosis of unresectable stage III NSCLC who underwent radical CRT followed or not by Durvalumab. Tumor response after CRT, pattern of relapse, overall and progression-free survival and toxicity profile were investigated. Results: Eighty-five patients met the inclusion criteria. Median age was 67 years (range 45–82 years). Fifty-two patients (61.2%) started sequential therapy with Durvalumab. The main reason for excluding patients from Durvalumab treatment was expression of PD-L1 < 1%. Only two patients presented a grade 4 or 5 pneumonitis. A median Follow-Up (FU) of 20 months has been reached. Forty-five patients (52.9%) had disease progression and 21 (24.7%) had a distant progression. The addition of maintenance immunotherapy confirmed a clinical benefit in terms of OS and PFS. Two-years OS and PFS were respectively 69.4% and 54.4% in Durvalumab group and 47.9% and 24.2% in no-Durvalumab group (p=0.015, p=0.007). Conclusions: In this real-world study, patients treated with CRT plus Durvalumab showed clinical outcomes and toxicities similar to the PACIFIC results. Maintenance immunotherapy after CRT has been shown to be safe and has increased survival of patients, in clinical practice.